Prototype Sistem Monitoring Nutrisi dan Tingkat pH Air pada Budidaya Hidroponik Sayur Pakcoy Menggunakan Teknologi Internet of Things (IoT) - Hamidah, Mafana Nur; Safitri, Nova Indah; Akbar, Dimas Wira; Uly, Olivia Sherly Indah; Kurnianto, Danny (Teknik Elektro Politeknik Negeri Padang, 2023)
The agricultural industry is critical in supplying food and fiber demands, but there is a demand-supply imbalance due to decreased land availability. Hydroponic techniques can be utilized to alleviate agricultural land loss by using water as a growing medium. Farmers must constantly examine plant condition and harvesting schedules. The pH of the water and nutrients are important indications for hydroponic farmers to monitor. Therefore, the implementation of the Internet of Things (IoT) allows farmers to conduct real-time monitoring more easily and regularly. IoT is defined as a system that allows integrated hardware to communicate with the internet network. The IoT device is built by attaching a NodeMCU 8266 microcontroller to an adapter, which provides electrical voltage while also regulating a water pump that delivers nutrients and water to plants. The acquired data is then transmitted to the blynk program, allowing real-time monitoring of the results via a smartphone. The present research system's usefulness and performance are improved by including pH and TDS sensors. The average accuracy of pH monitoring utilizing a pH sensor and a manual pH meter was 92.09%. Meanwhile, the average accuracy of nutrient monitoring utilizing TDS sensors and a TDS meter was 73.19%.